User engagement in public urban development projects - Ståhle, Matias; Vuorinen, Lauri; Toukola, Sebastian (Routledge, 2025)
Public urban development projects necessitate collaboration among stakeholders, particularly between municipalities and citizens. While existing research has focused more on collaboration between public and private stakeholders during project initiation, attention is shifting towards understanding user needs throughout the project lifecycle. This chapter investigates user engagement in two publicly procured construction projects. The multiple case study in the Finnish context explores how users are engaged in the planning process and in the finalisation and use phases of such projects. The findings highlight a variety of engagement practices for different users, ranging from more versatile and exploratory practices at the project's front end to more focused and formal approaches during the finalisation and use phases. Moreover, the results accentuate the importance and dynamic nature of user engagement throughout the project lifecycle. This chapter contributes to the discussion of user engagement in public urban development projects and provides recommendations for policy and practice for future urban development projects.
Citizen Participation in Sustainable Urban Development: A Framework for Engagement from the Nordics